2014
DOI: 10.1007/s12034-014-0032-3
|View full text |Cite
|
Sign up to set email alerts
|

High-temperature thermoelectric properties of Ag x Y y Ca2.8Co4O9 + δ ceramics

Abstract: Thermoelectric ceramics, Ag x Y y Ca 2⋅8 Co 4 O 9 + δ (0 ≤ x, y ≤ 0⋅15), have been prepared using a sol-gel method, followed by pressureless sintering. The phase structures and microstructures of oxides were investigated at room temperature. Thermoelectric properties including Seebeck coefficient, electrical conductivity and thermal conductivity were measured from 303 to 973 K. It was found that the samples contain nanostructured Ag phase with grain size of 100 nm. The Ag 0⋅05 Y 0⋅15 Ca 2⋅8 Co 4 O 9 + δ sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…where σ 0 is the pre-exponential term and E a is the Arrhenius activation energy. Linear relationships can be obtained at two temperature ranges: below 600 K, representing the small polaron-hopping conduction mechanism [15]; and above 600 K, indicating the semiconducting mechanism. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…where σ 0 is the pre-exponential term and E a is the Arrhenius activation energy. Linear relationships can be obtained at two temperature ranges: below 600 K, representing the small polaron-hopping conduction mechanism [15]; and above 600 K, indicating the semiconducting mechanism. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Many approaches regarding the enhancement of TE performance of calcium cobaltite (CCO) are conveyed through doping with alkaline metals [8,9], alkaline earth metals [10][11][12][13], transition metals [14,15], and/or rareearth metals [16] at Ca site. A comparison between some synthetic routes in the obtention of Ca 3 Co 4 O 9 phase shows that attrition milling and chemical methods produce very reactive precursors, reflected in the decomposition of CaCO 3 after a single heat treatment at 1023 K for 12 h. The attrition milling and the classical solid-state methods still contain small amounts of Ca 3 Co 2 O 6 phase while the chemical method can produce near pure Ca 3 Co 4 O 9 phase [17].…”
Section: Introductionmentioning
confidence: 99%
“…Zheng and Zeng utilized a concentric multihole spinneret. [80] When this side of the spinneret bearing holes had a basic flat surface, simulation study showed relatively lower electric field distribution in the central area compared to that toward the edges. Modifying the spinneret by creating a protrusion in the central area greatly boosted the electric field distribution to the central area.…”
Section: Hole Multijet Electrospinningmentioning
confidence: 92%
“…Reproduced with permission. [80] Copyright 2014, Springer. Cutaway view showing the cylindrical porous tube with its axis oriented vertically within a coaxial cylindrical collector (not to scale) b).…”
Section: Commercial Success Stories Of Electrospinning-based High-thrmentioning
confidence: 99%
“…For example, Zheng et al 23 reported to use the hydrothermal method to prepare the Fe3O4 nano-particle with the particle size of 27 nm with the surface active agent of AOT. This kind of particle has super-paramagnetism under room temperature.…”
Section: Introductionmentioning
confidence: 99%